RECQL4, Negatively Regulated by miR-10a-5p, Facilitates Cell Proliferation and Invasion via MAFB in Ovarian Cancer - Guo, Li; Li, Yingwei; Zhao, Chen; Peng, Jiali; Song, Kun; Chen, Long; Zhang, Ping; Ma, Hanlin; Yuan, Cunzhong; Yan, Shi; Fang, Yan; Kong, Beihua (Frontiers in Oncology, 2020)
The high frequency of somatic copy number alterations, as opposed to point mutations, is considered a unique feature of ovarian cancer. Amplification-dependent overexpression of RECQL4, which participates in DNA replication and repair, mediates the development of various cancers, but its pathobiological and clinical roles are poorly understood. Here, using bioinformatics analysis, RECQL4 amplification was found to occur in 27% of ovarian cancer samples in the TCGA cohort. RECQL4 was found to be upregulated and associated with a poor prognosis based on the immunohistochemistry staining of ovarian cancer. Functionally, RECQL4 overexpression increased proliferation and invasion of ovarian cancer cells. RECQL4 silencing had the opposite effects. In addition, RECQL4 knockdown enhanced the sensitivity of ovarian cancer cells to cisplatin and PARP inhibitor (PARPi). Further mechanistic investigations revealed that MAFB was a downstream target of RECQL4. The oncogenic effect of RECQL4 was attenuated after MAFB knockdown. Moreover, RECQL4 overexpression was negatively regulated by the tumour suppressor miR-10a-5p. Collectively, these findings indicate that genomic amplification and low expression of miR-10a-5p contribute to RECQL4 overexpression in ovarian cancer. This is the first study to reveal the oncogenic functions and clinical significance of RECQL4 in ovarian cancer.